Slow motion bias: Exploring the relation between time overestimation and increased perceived intentionality. (February 2023) - Hüttner*, Norman; Sperl*, Laura; Schroeger, Anna
Recent research on time perception has revealed that actions which are replayed in slow motion are perceived to take longer and rated to be more intentional (e.g., foul plays). Interestingly, the bias on duration estimations seems to disappear when information on the slow motion factor (i.e., the degree the video was slowed down) was provided. Here, we scrutinize the question whether also the intentionality bias disappears when explicit information about the slow motion factor is provided. To this end, two groups watched the same video clips, all displaying foul situations in a basketball match, in different video speeds. While the uninformed group saw the videos without further information, the informed group received additional information about the current slow motion factor. This study replicated the overestimation of original duration with increasing slow motion and indicated that this effect might be reduced when information about the slow motion factor is provided. However, despite generally lower intentionality ratings in the informed group, video speed information was not able to reduce the rise in intentionality ratings with increasing slow motion. Potential reasons and open questions regarding the nature and mechanisms behind these perceptual temporal biases (e.g., different time processing systems) are discussed.